EL REQUERIMIENTO DEL MARCO EPISTEMÓLOGICO EN LAS TESIS DE POST GRADO - Hurtado-Dianderas Smith, Eulogio (2006)
The epistemology as the theory of the knowledge is necessary and essential in the Post Degree thesis because it is sustained to a philosophical base for the defense of the proposed paradigm, considering that the paradigms are the sets of knowledge and beliefs that form a hegemonic theory in certain historical period. The paradigms are constituted by theoretical assumptions, laws and techniques of application that will have to adopt the researchers within a scientific community. Therefore each new paradigm contributes with answers to the enigmas that could not be solved with the previous paradigm, in addition of granting the academic support to the whole thesis. By these all, in current article it is presented the most important interrelationships between epistemology and scientific method generally employed in development of researching in this academic level. As a consequence, the Faculty of Administrative Sciences of this University must establish the requirement of the epistemological frame for all the Post Degree theses.